An analysis of the discretion of the SARS and the relevant factors considered following a request for the suspension of the payment of disputed tax in terms of section 164(3) of the Tax Administration Act 28 of 2011 - Van Wyk, Danielle (Stellenbosch : Stellenbosch University, 2015)
Thesis (MAcc)—Stellenbosch University, 2015.